Smart monitoring of helical thread mill process with a wireless tool holder and CNC information. (31st August 2022) - Matsui, Shota; Ozaki, Nobutoshi; Hirogaki, Toshiki; Aoyama, Eiichi; Yamamoto, Takamasa; Shindo, Masatoshi
ABSTRACT: Considered the characteristics of threading using a thread mill, which is an end-mill tool for threading using the helical interpolation motion of a machining centre for clarity .The tool tangential component force (principal cutting force) and radial component force acting on the thread mill during helical interpolation were measured using a piezoelectric dynamometer capable of measuring the four components of X-, Y-, and Z-directions and torque. In this report, a method to separate the thrusts using Equations (1)–(4) is proposed. Furthermore, the cutting force observed during thread cutting, conducted using the proposed method and a wireless holder, is analysed. Further, the phenomena that occur in rough cutting edges during thread cutting are validated. In addition, the analysis results of thread cutting are presented considering the relationship between the hardness of the work material and the cutting resistance. Finally, the measurement error between the wireless holder and the piezoelectric dynamometer and the consistency of each measuring machine are verified.